2014
DOI: 10.1007/s00049-014-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

Benzoquinones from scent glands of phalangiid harvestmen (Arachnida, Opiliones, Eupnoi): a lesson from Rilaena triangularis

Abstract: In case of disturbance, the phalangiine harvestman Rilaena triangularis (Eupnoi, Phalangiidae) emits a directed jet from large prosomal scent (“defensive”) glands. The pungent-smelling secretion was analyzed by gas chromatography–mass spectrometry and found to contain mainly 1,4-benzoquinone along with 1,4-naphthoquinone and caprylic (=octanoic) acid. While various alkylated benzoquinones are characteristic for the scent gland secretions of many grassatorean Laniatores, this is the first incidence of benzoquin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Among a multitude of components found in the extracts of eupnoans and dyspnoans herein analyzed (will be published elsewhere), nine quinonic compounds were detected, namely 1,4-benzoquinone (BQ), 1,4-naphthoquinone (NQ), 1,4-naphthalendiol (ND), 6-methyl-1,4-naphthoquinone (MNQ), 2-methoxy-1,4-naphthoquinone (MOQ), 2-methoxy-6-methyl-1,4-naphthoquinone (MMOQ), 4-chloro-1,2-naphthoquinone (CNQ), 2-methyl-9,10-anthraquinone (MAQ), and 2,3-dimethyl-9,10-anthraquinone (DMAQ) (Figure 1). All compounds were already known to us from previous studies (e.g., Raspotnig et al, 2005, 2010, 2015b) and were readily identified by comparison of GC-MS data to authentic reference compounds (analytical data in Table 1). For MMOQ, no authentic reference was available and the position of substituents (methoxy-group in position 2; methyl-group in position 6) is tentatively proposed in analogy to the substitution pattern of the remaining naphthoquinones (e.g., MNQ, MOQ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among a multitude of components found in the extracts of eupnoans and dyspnoans herein analyzed (will be published elsewhere), nine quinonic compounds were detected, namely 1,4-benzoquinone (BQ), 1,4-naphthoquinone (NQ), 1,4-naphthalendiol (ND), 6-methyl-1,4-naphthoquinone (MNQ), 2-methoxy-1,4-naphthoquinone (MOQ), 2-methoxy-6-methyl-1,4-naphthoquinone (MMOQ), 4-chloro-1,2-naphthoquinone (CNQ), 2-methyl-9,10-anthraquinone (MAQ), and 2,3-dimethyl-9,10-anthraquinone (DMAQ) (Figure 1). All compounds were already known to us from previous studies (e.g., Raspotnig et al, 2005, 2010, 2015b) and were readily identified by comparison of GC-MS data to authentic reference compounds (analytical data in Table 1). For MMOQ, no authentic reference was available and the position of substituents (methoxy-group in position 2; methyl-group in position 6) is tentatively proposed in analogy to the substitution pattern of the remaining naphthoquinones (e.g., MNQ, MOQ).…”
Section: Resultsmentioning
confidence: 99%
“…Secretion-loaded filter paper pieces were transferred into 50 µl of hexane and extracted for 30 min. This method of direct sampling of secretion was suitable for many Eupnoi, was applied to confirm the scent gland origin of certain compounds and has already been described in a previous paper in detail (Raspotnig et al, 2015b). The method could not be applied for Dyspnoi (that are reluctant to emit secretion).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding scent gland secretions, the chemical composition of exudates appears to reflect the phyletic lineages among opilionids. In detail, suborders are characterized by the presence of (1) naphthoquinones and methyl-ketones in the Cyphophthalmi (Raspotnig et al 2005 , 2012 ; Jones et al 2009 ); (2) naphthoquinones, anthraquinones, and certain acyclic ketones in the Dyspnoi (Raspotnig et al 2010 , 2014 ); (3) naphthoquinones and ethyl-ketones in the Eupnoi (Blum and Edgar 1971 ; Meinwald et al 1971 ; Jones et al 1976 , 1977 ; Wiemer et al 1978 ; Ekpa et al 1985 ; Raspotnig et al 2015 ), and (4) phenols, benzoquinones, terpenes, vinyl-ketones and nitrogen-containing compounds in the Laniatores (e.g., Eisner et al 1971 ; Segovia et al 2015 ; summarized in Raspotnig 2012 ).…”
Section: Introductionmentioning
confidence: 99%